Social apoptosis in honey bee superorganisms - Page P. (2017)
Eusocial insect colonies form superorganisms, in which nestmates cooperate and use social immunity to combat parasites. However, social immunity may fail in case of emerging diseases. This is the case for the ectoparasitic mite Varroa destructor, which switched hosts from the Eastern honeybee, Apis cerana, to the Western honey bee, Apis mellifera, and currently is the greatest threat to A. mellifera apiculture globally. Here, we show that immature workers of the mite's original host, A. cerana, are more susceptible to V. destructor infestations than those of its new host, thereby enabling more efficient social immunity and contributing to colony survival. This counterintuitive result shows that susceptible individuals can foster superorganism survival, offering empirical support to theoretical arguments about the adaptive value of worker suicide in social insects. Altruistic suicide of immature bees constitutes a social analogue of apoptosis, as it prevents the spread of infections by sacrificing parts of the whole organism, and unveils a novel form of transgenerational social immunity in honey bees. Taking into account the key role of susceptible immature bees in social immunity will improve breeding efforts to mitigate the unsustainably high colony losses of Western honey bees due to V. destructor infestations worldwide.